2021
DOI: 10.3390/diagnostics11020305
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of FreeStyle Libre Flash Glucose Monitoring System Implementation in Real Life Clinical Setting: A Prospective Observational Study

Abstract: Background: In this study, we investigated the effectiveness of FreeStyle Libre Flash Glucose Monitoring (FGM) implementation in a real life clinical setting with the emphasis on the effect of initial education on the use of the FGM system. Methods: This prospective observational study included 425 diabetes type 1 subjects followed up for 3 to 12 months (320 were followed up to 3 months, 267 up to 6 months and 147 up to period of one year). An FGM sensor was placed at study entry and all participants were educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Results of this study demonstrated significant improvement in glycemic management three months from isCGM initiation, which is consistent with clinical experience to date [ 25 , 26 , 27 , 28 ]. Significantly higher HbA1c measurements at baseline were seen in subjects with lower socioeconomic status; these results have also previously been seen in adults and children with T1DM [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 89%
“…Results of this study demonstrated significant improvement in glycemic management three months from isCGM initiation, which is consistent with clinical experience to date [ 25 , 26 , 27 , 28 ]. Significantly higher HbA1c measurements at baseline were seen in subjects with lower socioeconomic status; these results have also previously been seen in adults and children with T1DM [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 89%
“…Our concept, however, is not labour intensive nor resource‐ consuming for a clinic, and it is probably possible to replace some of the follow‐up visits with telephone consultations. Most other education concepts are more time‐consuming 18–20 …”
Section: Discussionmentioning
confidence: 99%
“…isCGM FSL appeared on the EU market in 2014 and is available in Croatia since September 2018. In a previous study, we showed in T1DM patients how 3 months of FSL use led to a significant drop in A1C mainly driven by those patients whose A1C was >7% (53 mmol/mol), and the improvement in A1C was mainly correlated to the increase in the number of scans per day [12].…”
Section: Introductionmentioning
confidence: 86%